Investigating awareness, fear and control associated with norovirus and other pathogens and pollutants using best–worst scaling - Farkas, Kata; Green, Emma; Rigby, Dan; Cross, Paul; Tyrrel, Sean; Malham, Shelagh K.; Jones, David L. (Nature Publishing Group, 2021)
Pollutants found in the water and air environment represent an ever-growing threat to human health. Contact with some air-, water- and foodborne pathogens (e.g. norovirus) results in gastrointestinal diseases and outbreaks. For future risk mitigation, we aimed to measure people’s awareness of waterborne and foodborne norovirus relative to other environment-associated pollutants (e.g. pesticides, bioaerosols, antibiotic resistant bacteria) and well-known risks (e.g. diabetes, dementia, terrorist attack). We used an online survey, which included a best–worst scaling component to elicit personal levels of control and fear prompted by norovirus relative to 15 other risks. There was a negative correlation between levels of fear vs. control for all 16 measured risks. Perceived infection control levels were higher amongst women compared to men and correlated with age and the level of qualification in both groups. Participants who had sought advice regarding the symptoms caused by norovirus appeared to have more control over the risks. Norovirus is associated with high levels of fear, however, the levels of control over it is low compared to other foodborne illnesses, e.g. Salmonella. Addressing this deficit in the public’s understanding of how to control exposure to the pathogen in an important health need.
Keywords: Environmental social sciences; Policy and public health in microbiology; Risk factors; Virology